? Physical Characteristics of Oil from Roots and Flowers of Mangifera indica ? ? (Biological Sciences - PJSIR, 2022)
Table 2. The confirmation of these methylated fatty acids wascarried out by the comparison of mass spectra of unknowncompounds with those ofNBS mass spectra library [14]. Therelative retention time (RR1) and relative percentages of occurrenceof their methylated fatty acids are also shown inTable 2.